Oil Prices and Macroeconomic on the Islamic Banking Performance in OPEC Member Countries - Effendi, Kharisya Ayu (International Journal of Energy Economics and Policy, 2018)
The purpose of this study was to determine the effect of oil price and macroeconomic factors on the Islamic banking performance. The data for this study were collected from secondary data from 2007 to 2016. The results of the analysis obtained are that each country has different characteristics so that it can have a different impact on the performance of Islamic banking. In addition, Islamic banking does not have an influence on oil prices and macroeconomic conditions because the market share of Islamic banking in the country is very small when compared to conventional banking. This means that the industry in the oil business uses funds in conventional banking is greater than Islamic banking. Because Iran, which uses 100% of Islamic banking in its business funding, found that oil prices have a huge influence on the Islamic banking performance. Keywords: oil prices, macroeconomics, performance, Islamic banking JEL Classifications: C1, E6, G21, Q41 DOI: https://doi.org/10.32479/ijeep.7098